Mitigating Disease Impacts in Amphibian Populations: Capitalizing on the Thermal Optimum Mismatch Between a Pathogen and Its Host - Hettyey, Attila; Ujszegi, János; Herczeg, Dávid; Holly, Dóra; Vörös, Judit; Schmidt, Benedikt R.; Bosch, Jaime (Frontiers in Ecology and Evolution, 2019)
Chytridiomycosis, a recently emerged infectious disease caused by the fungal pathogen Batrachochytrium dendrobatidis (Bd) in anuran amphibians has led to the most spectacular disease-borne loss of vertebrate biodiversity ever recorded in history. Unfortunately, the methods of mitigation that are available today are only practical in captive populations, and a method that could be applied in natural habitats at large spatial scales is lacking. We suggest here that the thermal tolerance mismatch between Bd and its ectothermic hosts coupled with the thermoregulatory behaviour of amphibians could be exploited in mitigation interventions combating Bd infection in situ. If microhabitats with elevated temperatures are made available in their natural environment, individuals taking advantage of the possibility to reach their preferred body temperature could critically lower their infection intensity or even clear the pathogen. We provide a basis for studying this approach by reviewing the evidence that supports the idea, describing how technical difficulties may be overcome, pointing out gaps in our knowledge that need to be filled by future studies, and listing presumable benefits and probable limitations of localized heating. The proposed approach has good potential to become an effective in situ mitigation method that can be easily employed in a wide taxonomic range of amphibians, while causing less collateral damage than any other method that is currently available. If so, it may quickly become a widely applicable tool of biodiversity conservation and may contribute to saving many amphibian populations and species from extinction in the next few decades.